(untitled) (Jurnal Destinasi Pariwisata, 2025)
This study aims to analyze the impact of tourism on the local community in Batur Selatan Village, Kintamani Sub-district, Bangli Regency. The village has become a prominent tourist destination due to its natural beauty and preserved local culture. Using a qualitative approach, data were collected through field observation, in-depth interviews with local residents, village officials, forest area managers, as well as literature review and documentation. The findings indicate that tourism has brought positive impacts such as increased income, expanded employment opportunities, the growth of local economic enterprises, and improved village infrastructure. However, several negative impacts were also identified, including social inequality, dependency on the tourism sector, cultural value shifts, and environmental pressures such as forest degradation and increased waste. These findings highlight the need for sustainable tourism management that actively involves the local community to minimize negative effects and ensure that the benefits of tourism are distributed fairly among all segments of the population. Furthermore, the study reveals a transformation in the socio-economic structure of the village, where traditional livelihoods such as farming have increasingly been replaced by tourism-related work. This shift has led to a redefinition of local identity and community relations, especially among younger generations. The commodification of culture for tourist consumption has also sparked concerns about authenticity and cultural preservation. Environmentally, the unregulated growth of tourism infrastructure poses a serious threat to the ecological balance of the village’s forested areas, which are central to its attraction. Therefore, this research underlines the importance of integrated planning, community-based tourism models, and regulatory policies that prioritize environmental conservation and cultural sustainability. A participatory approach is essential to maintain harmony between tourism development and the traditional values of the community, in line with the principles of sustainable and inclusive development.